1981
DOI: 10.1021/ic50222a030
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of the ferromagnetically coupled nickel dimer (C3H6N2H6)2[Ni2Cl8(H2O)2]

Abstract: C0)4, 62264-13-5; [Ph2PCH2PPh(¡-Pr)]Mo(CO)4, 62264-10-2; [Ph2PCH2PPh2]Mo(CO)4, 26743-81-7; [Ph2PCH2P(t-Bu)2]W(CO)4, 2] W(CO)4, 62264-14-6; [Ph2PCH2PPh(/-Pr)]W(CO)4, 62264-11-3; [Ph2PCH2PPh2] W(CO)4, 41830-14-2; [Ph2P(S)CH2P(i-Pr)2]Cr(CO)4, 62264-23-7; [Ph2P-(S)CH2PPh(i-Pr)]Cr(CO)4, 62263-99-4; [Ph2P(S)CH2PPh2]Cr(CO)4, 62264-01-1; [Ph2P(S)CH2P(i-Pr)2]Mo(CO)4, 62264-22-6; [Ph2P-(S)CH2PPh(¡-Pr)]Mo(CO)4, 62264-28-2; [Ph2P(S)CH2PPh2]Mo-(CO)4, 54340-52-2; [Ph2P(S)CH2P(/-Pr)2]W(CO)4, 62264-21-5; [Ph2P(S)CH2PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Previous studies on doubly chloro-bridged Ni(II) dimers showed that the magnetic interaction are predominantly ferromagnetic if the geometry of the metal centre is octahedral (Table 3), [26,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and the strength of the coupling varies from 3.48 to 14.59 cm À 1 , with only one exception where AF interaction is operative between the metal centres with high degree of distortion of Ni(II) centres from the octahedral geometry. [64] Tamayo et al have established that the strength of the ferromagnetic coupling become weaker with increase of the bridging angle from ideal value of 90°.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on doubly chloro-bridged Ni(II) dimers showed that the magnetic interaction are predominantly ferromagnetic if the geometry of the metal centre is octahedral (Table 3), [26,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and the strength of the coupling varies from 3.48 to 14.59 cm À 1 , with only one exception where AF interaction is operative between the metal centres with high degree of distortion of Ni(II) centres from the octahedral geometry. [64] Tamayo et al have established that the strength of the ferromagnetic coupling become weaker with increase of the bridging angle from ideal value of 90°.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…Our data provide us information that chloride (J = 6.84(10) cm À 1 ) is better magnetic coupler than cyanate ion (J = 5.31(4) cm À 1 ). If we look at the reported results, it is seen that J values (considering Ĥ = À 2JŜ 1 ⋅Ŝ 2 ) vary from 1.91 to 43.9 cm À 1 in doubly μ 1,1 -azido-bridged dinickel(II) complexes, [13][14][15][16][17][18][19][20][31][32][33][35][36][37][38][39][40][41][42][43][44][45][46] while the ranges are 1.7 to 6.85 cm À 1 [19,21,24] and 3.48 to 14.59 cm À 1 [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] for doubly μ 1,1cyanato-bridged and doubly μ-chloro-bridged analogues, respectively, and the trend of their average values is exactly replicated in the present study, that help us to conclude that μ 1,1 -azido is superior magnetic exchanger among them, followed by μ-chloro and μ 1,1 -cyanato.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…In these scheme, the transition energies involved in the denominators are defined as differences between the eigenvalues e of the SCF Hamiltonian AEp-^j -• tp -6q (5) This choice enables us to use the same transition energies for all the configurations corresponding to a given space function and gives simplifications in the energy corrections.16,20 With this definition, a degeneracy of the neutral |ab| or |ba| and ionic |aa| or |bb| determinants occurs and then the transition energy between magnetic orbitals A£a_b *s zero. To overcome this difficulty, we define this transition energy as the difference between the mean values of the exact Hamiltonian A£a_b = <|ab||5¥||ab|> -<|aá||77||aá|> (6) according to the Epstein-Nesbet (EN) definition.14,21 Zeroth Order. If we omit the closed shells, which play no part in the process, the zeroth-order eigenfunctions for the singlet and for the Sz = 0 component of the triplet state may be written…”
Section: Mo'smentioning
confidence: 99%
“…orbital degeneration is retained. [44][45][46][47][48][49][50][51] However, the interaction becomes antiferromagnetic when Ni(II) is pentacoordinated or placed in a highly distorted octahedral surrounding, as it seems to be the case of compound 6.…”
Section: Magnetic Propertiesmentioning
confidence: 99%